Analysis of optical switching in a Yb3+-doped fiber Bragg grating by using self-phase modulation and cross-phase modulation - Zang, Zhigang; Zhang, Yujun (Applied optics. Optical technology and biomedical optics, 2012)
The optical performances of the all-optical switching based on Yb3+-doped fiber Bragg grating (FBG) are investigated under the case of self-phase modulation (SPM) and cross-phase modulation (XPM). For the SPM case, the optical bistability of FBG under different parameters is investigated. It shows that the width of the hysteresis loop and threshold switching power are strongly dependent on the fiber grating length, fiber grating detuning, and coupling constant. For the XPM case, the expressions of the threshold switching power in the different detuning range are given. The influence of parameters about different detuning and coupling constant to the threshold switching power and extinction ratio are also studied. In comparison with the SPM case, the switching power of FBG under XPM case can be reduced to less than 20 mW by optimizing the parameters of FBG.